Some factors affecting dipped nitrile latex films - Mohd. Ghazaly H; Lai P F (Journal of Rubber Research, 2001)
Dipped Nitrile latex films were prepared by spontaneous gelation using a solution of ~28;calcium nitrate in water. When the pH of the compound was adjusted to >12 using 5 wt;KOH solution, the mechanical (tensile and tear) properties were found to be better compared with compounds prepared at pH~9. The tear properties were especially higher when the films were not leached, although the leached films gave a higher tensile strength. The nitrile latex films could be cured using sulphur or zinc oxide. Higher tearing resistance was obtained from the zinc oxide cured films although these films tend to show lower chemical resistance compared to the sulphur cured films. The zinc cured nitrile latex films also tend to give higher elongation at break values. Higher tear strength values were also observed for films filled with a stabilised fumed silica prepared at pH of 12 compared with other fillers such as silane-modified silica and titanium dioxide. Carboxylate groups were identified by FTIR and Raman spectroscopy in films obtained from the latexes whose pH values were raised to 12; the carboxylic moieties were observed in films obtained from latexes at pH 9.
Keywords: Compounding; Dipped nitrile latex; FTIR; Latex films; Mechanical properties; Raman spectroscopy; SEM; STEM